The Design and Development of an Open and Flexible E-Training System for the Creation of Learning Organizations - Suraya, H.; Nur, A.N.A.Y.; Mohamad, T.I.; Leong, O.; Hong, J.J. (2008)
In the rapid development of global market, there is an urgent need for organization to provide training to its employees to ensure their continuous competence in handling their task. The challenge from this scenario is to find a way to enforce employees to enhance their knowledge and skills from time to time by developing an e-training system. Applying the learning organization model through the e-training system would indirectly introduce the learning organization concept into the organization. Apart from etraining, knowledge management system was also implemented to ensure the effectiveness of learning organization. This research is about the design and development of an e-training system using University of Malaya (UM) as the case study. The system would offer Balanced Scorecard (BSC) and Technopreneurship as the sample courses. The discussion scope of this paper is limited to the development of the system framework and architecture which form the initial stage of this research work. Based on the findings, it is shown that e-training system can be used as a tool to create learning organizations in companies and educational institutions.